Sofrimento psíquico no trabalho: um estudo com encarregados de uma organização familiar de Fortaleza (CE) - Bastos, Elaine Marinho (2014)
The present study deals with issues related to mental health work and relating them to everyday leaders in family firms. The questioning came because of reports and the perception of a possible relationship between psychological distress cases and the daily work of these professionals. Before starting the research, it was made a study with theoretical topics related to this work, such as psychological distress , Psychopathology and Psychotherapy, Family Organizations and leadership. Starting from assumptions which showed the characteristics of family organizations, with their peculiar management practices, such as triggering of psychological distress and even in the face of defensive strategies, it would lead to absenteeism and somatization. The research methodology was qualitative, descriptive, seeking to know the reality of family organization and investigate the relationship between experiences of pleasure and suffering at work of the leaders on the management in a family organization, giving them the opportunity to exhibit the work perceptions that they lead everyday and pleasure and pain experienced in comparison with the work done . Interviews and focus groups were conducted, in order to collect data that could identify the presence and type of manifestation of psychological distress of the leaders; describe the characteristics of management; analyze the relationship that managed to family organization and relate the work of leaders with their psychological distress, as well as its defense strategies to deal with this suffering. After content analyzes, five categories were found: Work – unpredictable changes and crossings, pointing work, as time employment, beyond the scope of the organization and experiences that affect the family and leisure; Threshold between pleasure and suffering, noting that there is a threshold between the situations of pleasure and suffering in the work of the leaders; Life - charge and easily overwhelmed by the experience of people management; Contexts of family organization, with its peculiarities, reinforcing the existence of limitations on management leadership and advocacy strategies that are used to not getting sick . The speech brought the obtained symbolic experience determined by contextual scenario, before the central theme of suffering and pleasure in work, featuring experiences of pleasure and pain of leadership in the peculiar context of family organization researched.